Content of antenatal care and perception about services provided by primary hospitals in Nepal: a convergent mixed methods study. (17th March 2021) - Acharya, Yubraj; James, Nigel; Thapa, Rita; Naz, Saman; Shrestha, Rishav; Tamang, Suresh
Abstract: Background: Nepal has made significant strides in maternal and neonatal mortality over the last three decades. However, poor quality of care can threaten the gains, as maternal and newborn services are particularly sensitive to quality of care. Our study aimed to understand current gaps in the process and the outcome dimensions of the quality of antenatal care (ANC), particularly at the sub-national level. We assessed these dimensions of the quality of ANC in 17 primary, public hospitals across Nepal. We also assessed the variation in the ANC process across the patients' socio-economic gradient. Methods: We used a convergent mixed methods approach, whereby we triangulated qualitative and quantitative data. In the quantitative component, we observed interactions between providers (17 hospitals from all 7 provinces) and 198 women seeking ANC and recorded the tasks the providers performed, using the Service Provision Assessments protocol available from the Demographic and Health Survey program. The main outcome variable was the number of tasks performed by the provider during an ANC consultation. The tasks ranged from identifying potential signs of danger to providing counseling. We analyzed the resulting data descriptively and assessed the relationship between the number of tasks performed and users' characteristics. In the qualitative component, we synthesized users' and providers' narratives on perceptions of the overall quality of care obtained through focus group discussions and in-depth interviews. Results: Out of the 59 tasks recommended by the World Health Organization, providers performed only 22 tasks (37.3%) on average. The number of tasks performed varied significantly across provinces, with users in province 3 receiving significantly higher quality care than those in other provinces. Educated women were treated better than those with no education. Users and providers agreed that the overall quality of care was inadequate, although providers mentioned that the current quality was the best they could provide given the constraints they faced. Conclusion: The quality of ANC in Nepal's primary hospitals is poor and inequitable across education and geographic gradients. While current efforts, such as the provision of 24/7 birthing centers, can mitigate gaps in service availability, additional equipment, infrastructure and human resources will be needed to improve quality. Providers also need additional training focused on treating patients from different backgrounds equally. Our study also points to the need for additional research, both to document the quality of care more objectively and to establish key determinants of quality to inform policy.